The Jacksons' Debate - Marcus Vinicius Neves (Vernacular: New Connections in Language, Literature, & Culture, 2025)
The Jacksons’ Debate” explores ethical dilemmas through an alien civilization considering human consumption. This philosophical sci-fi story examines sentience, moral responsibility, and societal progress from a unique perspective. Blending dark humor with social commentary, it challenges readers to reflect on human behavior and ethical decision-making in the face of necessity and scientific advancement.
Keywords: Philosophical Fiction